Kelimpahan dan Diversitas Aktinomisetes Tanah Taman Nasional Gunung Ciremai Jawa Barat - Nurkanto, Arif (Perhimpunan Biologi Indonesia, 2009)
ABSTRACTThe Abundance and Diversity of Soil Actinomycetes from Ciremai National Park West Java.Actinomycetes of soil samples from Mount Ciremai National Park, West Java were been isolatedby Sodium Dodecyl Sulphate Yeast Extract (SDS YE) method in Humic Acid Vitamin Agar(HVA) medium. The colonies of actinomycetes were counted based on Total Plate Count(TPC). Diversity of actinomycetes were identified based on spore, chain spore, pigmentation,hypha and aerial hypha formation. The abundance of actinomycetes were 3,50 x104 â 71,50 x104CFU/g soil. Seven genus of actinomycetes were found, they were Streptomyces, Nocardia,Micromonospora, Microbiospora, Actinomadura, Actinoplanes, and Microtetraspora. Mostof them were distributed in 900 until 2500 m height above sea level. Streptomyces only knownin 2700, 2900 and 3057 m above sea level. Population of Streptomyces were predominant in allsoil types according to height, but were highest in 2500 m asl.Key words: Actinomycetes, fungi, Mount Ciremai, diversity, abundance.